Role of Training in Women for Employment: A Thematic Study - Pandit, Asmita (Journal of Technical and Vocational Education and Training, 2025)
The vocational training is a crucial approach for empowering women, encouraging economic independence, and building social equality, particularly in the settings where conventional gender norms restrict women's access to formal labor markets. This study indicates that vocational training has developed a good level of self-esteem in women along with decision-making skills and participation in household and community decisions. The study uses a qualitative approach with thematic analysis to explore the complex relationships among vocational training, women's empowerment, and labor market outcomes. After reviewing recent national and international researches, the findings reveal that vocational training not only improves technical abilities but also increases confidence, decision-making capacity, and social recognition within families and communities. Furthermore, these efforts encourage entrepreneurial desires and economic independence. However, the ultimate goals of such initiatives are hampered by challenges such as inadequate market alignment, lack of post-training support, and limited access to funding. These findings highlight the importance of quality instruction, closer alignment with industry, and improved support mechanisms to guarantee that such projects are long-term and effective. It is advised that follow-up mentorship, financial literacy, and networking platforms are necessary to assist women in transitioning from training to stable job or self-employment. This study focuses on comprehensive, market-relevant vocational training programs as critical interventions for bridging gender gaps in the workforce and promoting women's social and economic empowerment in Nepal. Thus, the research provides an important understanding for policymakers and program developers in constructing sustainable and impactful training programs for women.